2020
DOI: 10.3329/imcjms.v13i2.45279
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of healthy coastal fishermen of Bangladesh

Abstract: Background and objectives: Vitamin D deficiency is now a global concern. Industrialization, urbanization and the decreasing participation in outdoor activities, with consequent sunlight deprivation, are thought to be the key factors in the increasing prevalence of vitamin D deficiency among general population of many countries. It is presumed that healthy, adequately sun-exposed people should maintain adequate vitamin D levels. However, studies within this population are scarce. Hence, this study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…According to various studies around 51-100% of the different groups of population suffered from low vitamin D level [3,[6][7][8]. In spite of adequate sun exposure, a recent study showed that about 70.7% people living in coastal area of Cox's Bazar, Bangladesh had low serum 25(OH)D level [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to various studies around 51-100% of the different groups of population suffered from low vitamin D level [3,[6][7][8]. In spite of adequate sun exposure, a recent study showed that about 70.7% people living in coastal area of Cox's Bazar, Bangladesh had low serum 25(OH)D level [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, vitamin D deficiency is common in all age-groups and higher in females [1]. A recent study reported vitamin D deficiency was 71% among adequately sunlight exposed coastal fisherman of Bangladesh [3]. Despite abundant sunshine, the high prevalence of vitamin D deficiency is a mystery in a subtropical country like Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that variants of rs10741657 in CYP2R1 gene may give rise to low serum 25(OH)D level irrespective of adequate sun exposure and healthy diet [15]. Despite abundant sun exposure low serum 25(OH)D level has been found among most Bangladeshi people [8,9]. The genetic influence of rs10741657 of CYP2R1 on low serum 25(OH)D level has never been investigated before in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%